Erratum: Development and Priority Selection of Marketing Strategies for Pangas Catfish Skin Chips at Gatiga Snack MSMEs - Eka Novriyanti; Teny Sylvia; Noveliska Br Sembiring (Department of Agroindustrial Technology, Faculty of Agricultural Technology UGM, 2026)
This Erratum relates to the following article:Novriyanti, E., Sylvia, T., Sembiring, N.B., 2025. Development and Priority Selection of Marketing Strategies for Pangas Catfish Skin Chips at Gatiga Snack MSMEs. Agroindustrial Journal 12(1), 43–53. https://doi.org/10.22146/aij.v12i1.106078The publisher regrets that, due to a production error, the publication metadata on page 1 of the published PDF version of the article (DOI: 10.22146/aij.v12i1.106078) contained incorrect dates. The incorrect information appeared as: “Received: May-27-2025; Accepted: June-26-2025; Published: June-30-2025”. The correct dates are: “Received: April 17, 2025; Accepted: June 26, 2025; Published: June 30, 2025”.The editorial office regrets the error.